Analisis Penerapan BSC (Balanced Scorecard) sebagai Alat Manajemen Strategi pada Rumah Sakit Umum Daerah dr. H. Yuliddin Away Tapaktuan - Purwadhi Purwadhi; Yani Restiani Widjaja; Salwiyadi Salwiyadi; Salia Marvinia (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Hospitals as healthcare institutions, are required to deliver high-quality, efficient, and sustainable services through proper strategic management. Dr. H. Yuliddin Away Regional General Hospital, a type B referral hospital in Aceh, faces challenges such as limited resources, increasing demands for service quality, and regulatory changes in the healthcare sector. This study aims to analyze the implementation of the BSC (Balanced Scorecard) (BSC) as a strategic management tool to improve hospital performance. The BSC is employed because it integrates financial and non-financial indicators through four perspectives: financial, customer, internal business processes, and learning and growth. This research applies a descriptive qualitative approach using a case study at Dr. H. Yuliddin Away Hospital. Data were collected through interviews, observations, and documentation, and analyzed using content analysis. The findings show that the hospital has adopted the BSC since 2021 with key performance indicators aligned to its vision and mission. From the financial perspective, the operational cost ratio achieved the target (65% against ≤70%). The customer and internal process perspectives did not fully meet the targets, as patient satisfaction (4.1 vs. ≥4.2) and average service time (62 minutes vs. ≤60 minutes) revealed small gaps. Conversely, the learning and growth perspective exceeded expectations with six staff training sessions per year. Overall, the implementation of BSC has had a positive impact on transparency, accountability, and interdepartmental coordination, while also fostering service innovation. However, challenges remain, including limited managerial understanding, budget constraints, and organizational resistance to change. The study concludes that BSC is an effective tool for improving hospital performance, though further efforts are needed to enhance patient satisfaction and service efficiency.